Geography and Employer Recruiting - Russell Weinstein (Institute of Labor Economics (IZA), 2017)
I analyze whether reducing geographic distance to high-wage jobs increases access to those employment opportunities. I collect office locations and campus recruiting strategies for over 70 prestigious banking and consulting firms, from 2000 to 2013. Using an event-study framework, I find firms are 2 times more likely to recruit at local universities after opening a nearby office, and 6 times more likely outside industry clusters. New target campuses outside industry clusters are less academically selective. The results suggest place-based policies may improve access to high-wage firms, and also suggest the importance of a university's local labor market for post-graduation outcomes.
Keywords: J23; J61; I26; 330; employer recruiting; local labor markets; returns to college